Trade-climate nexus: A systematic review of the literature - Jeremiás Máté Balogh; Tamás Mizik (Economies, 2021)
In the climate-trade debate, moderate attention is dedicated to the role of trade agreements on climate. In turn, trade agreements could help countries meet climate goals by removing tariffs, harmonizing standards on environmental goods, and eliminating distorting subsidies on fossil fuels. This paper aims to provide an overview of the role of trade agreements on climate-change mitigation. This systematic literature review is based on the international economic literature published between 2010 and 2020. This literature review underlines that the effectiveness of the trade agreements and WTO negotiations on emission reduction is weak. This is due to different national interests and protectionism. The elimination of trade barriers stimulates trade, but this may also raise greenhouse gas emissions and cause other environmental problems (e.g., deforestation). Furthermore, this article points out that emission leakage is also a crucial issue hindering the success of global climate agreements on greenhouse gas reduction. The greatest beneficiaries of the trade agreements are usually the largest GHG emitters, such as China, the US, and the EU. By contrast, developing countries are in a weaker position regarding climate-trade negotiation. The literature review offers policy solutions which can contribute to emission reduction and tools for stimulating a trade-related climate-change abatement policy.
Keywords: 330; carbon dioxide emission; climate change; literature review; trade agreements; WTO